PELATIHAN MANAJEMEN USAHA DALAM UPAYA PENGEMBANGAN USAHA BORDIR DI NAGARI SINGGALANG KABUPATEN TANAH DATAR - Yessy Andriani; Dian Yuni Anggraeni; Laksmi Dewi (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2024)
This activity aims to provide business management training for embroidery businesses in Nagari Singgalang, Tanah Datar. This aims to ensure that the business can be managed well so that it provides good business profits. The method used in this service activity is the lecture and training method. The lecture method is given in the form of counseling using public participative and woman participative techniques in economics. This method focuses training on female embroidery craftsmen. In training activities, business actors are given business management training which includes capital management, production management and preparation of financial reports. Partner businesses are given direct assistance in managing their business starting from creating a business organizational structure, creating Standard Operational Procedures (SOP) for business activities and creating business financial reports. The output resulting from this activity is that the partner business has an organizational structure for the partner embroidery business where each member of the company has their own duties. The training also produces Standard Operational Procedures (SOP) for every embroidery business activity starting from SOPs for ordering, production and delivery or sales. Apart from that, partner businesses also have simple business financial reports. Thus, this training has increased the ability of business partners to manage their business so that business management becomes more organized and focused. This certainly makes it easier for business managers to manage their business. As a result, businesses achieve efficiency in production. Good business management will also make it easier to develop your business in the future.